Posthuman Publics: Emerging Research in Human-Machine Communication - Banks, Jaime; Edwards, Autumn; Joblin, Anna; Lewis, Seth; Edwards, Chad; Westerman, David; Spence, Patric; Guzman, Andrea (AoIR Selected Papers of Internet Research, 2017)
In both its academic and lay uses, for centuries “public” has referred to "people." From an Aristotelian perspective, publics of varying scale emerge as speech (or logos) binds people together, catalyzing and materializing through dyadic and larger-scale interactions. But how might publics emerge when some interlocutors are not people, exactly, but other types of social agents – as information and communication technologies gain increased agency, transitioning from things we communicate through to social actors we communicate with? This panel approaches these questions through empirical reports of four studies addressing the implications of human-machine communication at three levels – individual perceptions, dyadic interactions, and commercial and institutional dynamics – and accounts for interactions with and framings of social robots, algorithms, and artificial intelligence.